Exploiting the Expressiveness of Cyclo-Static Dataflow to Model Multimedia Implementations. (21st June 2007) - Denolf Denolf, Kristof Kristof; Bekooij Bekooij, Marco Marco; Cockx Cockx, Johan Johan; Verkest Verkest, Diederik Diederik; Corporaal Corporaal, Henk Henk
Abstract : The design of increasingly complex and concurrent multimedia systems requires a description at a higher abstraction level. Using an appropriate model of computation helps to reason about the system and enables design time analysis methods. The nature of multimedia processing matches in many cases well with cyclo-static dataflow (CSDF), making it a suitable model. However, channels in an implementation often use for cost reasons a kind of shared buffer that cannot be directly described in CSDF. This paper shows how such implementation specific aspects can be expressed in CSDF without the need for extensions. Consequently, the CSDF graph remains completely analyzable and allows reasoning about its temporal behavior. The obtained relation between model and implementation enables a buffer capacity analysis on the model while assuring the throughput of the final implementation. The capabilities of the approach are demonstrated by analyzing the temporal behavior of an MPEG-4 video encoder with a CSDF graph.